An Investigation on Teachers Skills in Educational Clinics (Ambulatory Setting) in Isfahan University of Medical Sciences - R Mollabashi (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Medical education has been shifted from the theoretical classes and hospital wards to the outpatient clinics and ambulatory settings. Regarding the existing problems in this type of education, this study was done to investigate teaching-learning process in educational ambulatory settings of medical school in Isfahan University of medical sciences, Iran.METHODS: This cross-sectional study with random cluster sampling was conducted on 45 teachers of Isfahan University of medical sciences within 2007-2008. The data related to teachers skills in domains of pre teaching, within teaching and post teaching were collected by a researcher made check list (yes/no questions) with confirmed validity and reliability.FINDINGS: The findings revealed that teachers skills in pre teaching, some post teaching (finalizing the educational material and giving feed back to learners) and within teaching (making relation between past and newly learned materials) domains were weak. Meanwhile, their skill in items such as physical exam and interviewing the patients (eye contact, respecting privacy and appropriate cover of the patients) were excellent.CONCLUSION: The findings showed that teachers were weak in some teaching skills such as pre teaching, post teaching and within teaching. So, holding related educational programs seems necessary to enhance teachers knowledge and function in teaching domains.